Comprehensive model for rotary wing unmanned aerial vehicle - Olcer, F.E. (My University, 2015)
Comprehensive model of a rotary wing unmanned aerial vehicle is built and analyzed in this study. It is a conventional rotorcraft, except its size. It makes use of a fly-bar system providing some level of stabilization in the pitch and roll motions as well as alleviating control loads, therefore special attention is given on the modeling of this system. Its model is built using FLIGHTLAB commercial software by adopting its full rotorcraft template and customization by increasing the number of rotors to accommodate for fly-bar system, tuning the maneuver wake distortion model and generating custom controls associated with the fly-bar/main rotor interactions. Analyses are carried out to highlight nonlinear effects associated with the fly-bar mechanism which is a typical component used on the small size unmanned rotary vehicles.
Keywords: Flight Mechanics